Luis Eduardo Valcárcel, the educator. The "Lake Titikaka Experiment" and "Geosocial Units" (1945): El "Experimento del Lago Titikaka" y las "Unidades Geosociales" (1945) (Revista Peruana de Investigación Educativa, 2023)
The following article aims to study Luis Eduardo Valcárcel Vizcarra as an educator and pioneer in the management of educational projects in the Andean region. Although Valcárcel's educational contribution has been partially published, this article aims to expand the information on the beginnings of his participation in the educational field, whose work was also shared with his political concerns. The appointment as Minister of Education in 1945 and later his appointment as director of the Peruvian Indigenist Institute in 1947 were events that allowed the execution of the "Lake Titicaca Experiment" with the aim of structuring indigenous peasant education in "Geosocial Units" and solving this way, the dispersion and isolation that the school suffered in the Andes in the middle of the 20th century.